Workshop Penguatan Tata Kelola UMKM Untuk Meningkatkan Keberlanjutan Usaha - Fangela Myas Sari; Siska Dewi; Nur Rokhman (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2023)
Indonesia's development and financing for its country comes from the income of MSMEs in Indonesia. MSMEs are the economic cycle in Indonesia and MSMEs have a very high influence on improving the economy in Indonesia. More entrepreneurs and MSMEs will increase the economic value of a country, namely Indonesia, because the economy will grow in proportion to the growth of MSMEs with MSMEs, people are required to become entrepreneurs and as a producer and is expected to be able to import its products abroad to increase income from abroad and domestically. The survival of MSMEs is very important for the continuity of MSME businesses, for this reason the government provides various kinds of stimuli so that MSMEs are able to survive under certain conditions, especially during the Covid-19 pandemic. MSMEs need to make improvements in terms of financial governance. This understanding starts from an early age, namely in the MSME environment to support government programs that intensify calls for Indonesian people to comply with reporting which plays a very important role in the country's development. The main problem obtained from observations of MSMEs in Api-api village, Wonokerto is that they do not understand financial governance for MSME entities for business sustainability, so it is necessary to hold a workshop regarding strengthening financial governance of MSMEs to improve business sustainability in Api-Api Village, Kec. Wonokerto Regency Pekalongan. Goals and targets of community service in Api-Api Village, Kec. Wonokerto Regency Pekalongan is so that the public understands good financial governance and how to prepare financial reports for community businesses in Api-Api Village, Kec. Wonokerto Regency Pekalongan. The number of participants was 30 MSME business actors. The implementation method is carried out by presenting workshop material directly (offline) in Api-Api Village, Kec. Wonokerto Regency Pekalongan. The output of this community service is in the form of scientific journal publications in the ITS NU Pekalongan Community Service Journal and cinematic videos of the implementation of community service.